Предмет: Алгебра,
автор: matveeva0022
Помогите решить
Ответы
Автор ответа:
1
4/(x+3)²+6/(x-3)(x+3)-1/(x-3)=0
x≠3 U x≠-3
4(x-3)+6(x+3)-1*(x+3)²=0
4x-12+6x+18-x²-6x-9=0
x²-4x+3=0
x1+x2=4 U x1*x2=3
x1=1
x2=3 не удов усл
x≠3 U x≠-3
4(x-3)+6(x+3)-1*(x+3)²=0
4x-12+6x+18-x²-6x-9=0
x²-4x+3=0
x1+x2=4 U x1*x2=3
x1=1
x2=3 не удов усл
Похожие вопросы
Предмет: Русский язык,
автор: Gcxfgbbcc
Предмет: Қазақ тiлi,
автор: shynybekovadana
Предмет: Русский язык,
автор: erlachovaangel
Предмет: Алгебра,
автор: Forwator
Предмет: Алгебра,
автор: PRO100NIKITA2017